Digital Technology Adoption and Online Marketing Strategies as Drivers of Consumer Purchase Decisions with the Moderating Effect of Service Quality - Awaluddin, Muhammad (Sinergi International Journal of Management and Business, 2025)
This study investigates how digital technology adoption and online marketing strategies drive consumer purchase decisions, with service quality examined as a moderating variable. Employing a quantitative explanatory design, data were collected from 200 Indonesian undergraduate students who actively use the Shopee e-commerce platform. Measurement items were adapted from established scales and analyzed through Principal Component Analysis (PCA) and moderated regression analysis. The results show that both digital technology adoption and online marketing strategies have significant positive effects on consumer purchase decisions. More importantly, service quality not only exerts a direct influence but also strengthens the relationships between technology, marketing, and consumer behavior. The proposed model explains 47.2% of the variance in purchase decisions, demonstrating moderate explanatory power. This research contributes to the literature by extending previous studies that primarily examined direct relationships. It introduces service quality as a moderating mechanism that enhances the effectiveness of digital and marketing innovations. Practically, the findings offer strategic insights for e-commerce platforms to integrate technological adoption, marketing personalization, and high-quality service delivery in order to build consumer trust and encourage sustainable purchasing behavior.